PERAN WISATA DESTINASI ALAM SEBAPO MUARO JAMBI DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT SEKITAR DALAM KONTEKS ISLAM - Aldo Juni Karya Pratama; Bambang Kurniawan (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2025)
Sebapo Nature Tourism is a tourist destination located in Muaro Jambi Regency and holds significant potential for boosting the economic growth of the surrounding community. This destination not only offers natural beauty but also provides an empowerment space for micro-entrepreneurs, such as food vendors, service providers, and local workers. This study aims to determine the role of Sebapo Nature Tourism in improving the community's economy and identify the obstacles faced in its management process, viewed from an Islamic economic perspective. This study used a qualitative descriptive approach, with data collection techniques including interviews, observation, and documentation of vendors, employees, and tourism managers. The results show that the presence of Sebapo Nature Tourism has had a direct impact on increasing the income of the surrounding community, creating employment opportunities, and the emergence of business models that prioritize the values of honesty, responsibility, and blessings in accordance with Islamic economic principles. However, several obstacles remain in the management process, such as limited supporting facilities, lack of human resource training, suboptimal digital promotion, and unequal community involvement. Therefore, a Sharia-based development strategy that actively involves the local community is needed to ensure sustainable economic benefits.